2020
DOI: 10.1007/s00424-020-02439-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporters in the small intestine in health and disease

Abstract: Absorption of monosaccharides is mainly mediated by Na +-D-glucose cotransporter SGLT1 and the facititative transporters GLUT2 and GLUT5. SGLT1 and GLUT2 are relevant for absorption of D-glucose and D-galactose while GLUT5 is relevant for D-fructose absorption. SGLT1 and GLUT5 are constantly localized in the brush border membrane (BBM) of enterocytes, whereas GLUT2 is localized in the basolateral membrane (BLM) or the BBM plus BLM at low and high luminal D-glucose concentrations, respectively. At high luminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(173 citation statements)
references
References 427 publications
(700 reference statements)
2
146
1
2
Order By: Relevance
“…When the concentration of glucose is low in the intestinal lumen, only SGLT1 is located in the apical side to transport it. Nonetheless, if the glucose concentration is high, GLUT2 is also located in the apical side to support glucose absorption [ 28 ]. Glucose enters from the apical side to the basolateral side of the small intestine, confirming the functionality of the glucose transporters and the gut sacs’ viability [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the concentration of glucose is low in the intestinal lumen, only SGLT1 is located in the apical side to transport it. Nonetheless, if the glucose concentration is high, GLUT2 is also located in the apical side to support glucose absorption [ 28 ]. Glucose enters from the apical side to the basolateral side of the small intestine, confirming the functionality of the glucose transporters and the gut sacs’ viability [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glucose enters from the apical side to the basolateral side of the small intestine, confirming the functionality of the glucose transporters and the gut sacs’ viability [ 29 , 30 ]. However, if GLUT2 is located on the apical side, a low opposite glucose transport is observed [ 28 ] ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we observed significant differences in glucose absorption between enteroids from the BS naïve lean subjects and those from the post-BS patients, despite the lack of significant differences in the expression levels of sugar transporters between these two groups. Additional consideration for differences in signaling, intracellular localization, and subcellular trafficking could contribute to different glucose-absorption profiles [ 23 , 59 ]. Dynamic regulation of glucose transport by protein trafficking has been reported for GLUT4 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary carbohydrates are digested in the small intestine into glucose, galactose, and fructose and then absorbed by enterocytes. Sodium–glucose co-transporter (SGLT)1, glucose transporter (GLUT)5, and GLUT2 are responsible for the transport of glucose, galactose, and fructose across the brush border membrane or basolateral membrane [ 70 ]. A loss-of-function study using a gene knock out mouse model suggested that SGLT1 is important for fast glucose absorption; however, the presence of GLUT2 has not been shown to have any role in either apical glucose influx or incretin secretion [ 71 ].…”
Section: Dietary and Microbial Metabolites Produced In The Gastroimentioning
confidence: 99%